Flexible ECG circuit fabrication and application using vinyl cutting technique - Noor Syazwana Sahar; Nurul Ashikin Abdul-Kadir; Fauzan Khairi Che Harun (Bulletin of Electrical Engineering and Informatics, 2020)
The aim of this study is to prove the capability of vinyl cutting technique to cut the conductive traces of electronic circuit layout which used a copper tape (Copper tape 1181 from 3M) on flexible substrate to replace the method of using nano-scale particle material. A wireless electrocardiography (ECG) circuit was integrated and fabricated on flexible substrate, namely a polyethylene terephthalate (PET) substrate by using vinyl cutting method to produce the conductive line traces. After that, the fabricated circuit is used for acquiring ECG signals from a patient simulator and human subjects to measure the performance differences and compatibility as a wearable device. In the data processing stage, ECG data were denoised using sym20 from Wavelet Transform tool provided by MATLAB. Then, Signal-to-noise-ratio (SNR) was calculated and used as the signal quality indicator. At the end of the study, flexible circuit performance was compared to MIT-BIH Arrhythmia database and it shows that there is no significance difference between both. In conclusion, vinyl cutting method shows a promising fabrication output on PET substrate as the performance of both flexible ECG circuit is comparable with rigid ECG circuit by a previous study.